Implementasi Berpikir Historis dalam Pembelajaran Sejarah di SMA Negeri 8 dan SMA Negeri 10 Samarinda - Syahputra, Muhammad Ilham; Purwanta, Hieronymus; Djono (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Historical thinking is a competency that students must master in history learning. This study focuses on the first competency, diachronic (chronological) thinking. The purpose of this study is to analyze the implementation of historical thinking, particularly diachronic (chronological) thinking, in history education at state senior high school 8 Samarinda and state senior high school 10 Samarinda. This study uses a qualitative research method with a case study approach, and data collection is conducted through classroom observation, in depth interviews, and document analysis. The results of the study indicate that both schools have implemented historical thinking in history education. This is evident from the teachers good understanding of the implementation of historical thinking, which has been carried out because both teachers always emphasize the importance of understanding chronology in history education. Despite obstacles such as dependence on AI, learning that still focuses on memorization, and a lack of literacy in history education. In conclusion, historical thinking, particularly diachronic (chronological) thinking in history education, is very important because it aims to enhace students critical thinking in history education.